2019
DOI: 10.2174/1568009619666190620114928
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shcbp1 in Signaling and Disease

Abstract: Src homolog and collagen homolog (Shc) proteins have been identified as adapter proteins associated with cell surface receptors and have been shown to play important roles in signaling and disease. Shcbp1 acts as a Shc SH2-domain binding protein 1 and is involved in the regulation of signaling pathways, such as FGF, NF-κB, MAPK/ERK, PI3K/AKT, TGF-β1/Smad and β -catenin signaling. Shcbp1 participates in T cell development, the regulation of downstream signal transduction pathways, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…Recent studies have shown that SHCBP1 acts as a Shc SH2domain binding protein 1 and is involved in the regulation of various signaling pathways including MAPK, PI3K/AKT. NF-kB, MAPK/ERK, b-catenin, and TGF-b1/Smad pathways (7). SHCBP1 has been demonstrated to play important roles in different types of cancer, such as breast cancer, synovial sarcoma, gastric cancer, and lung cancer (12-14, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that SHCBP1 acts as a Shc SH2domain binding protein 1 and is involved in the regulation of various signaling pathways including MAPK, PI3K/AKT. NF-kB, MAPK/ERK, b-catenin, and TGF-b1/Smad pathways (7). SHCBP1 has been demonstrated to play important roles in different types of cancer, such as breast cancer, synovial sarcoma, gastric cancer, and lung cancer (12-14, 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, unveiling molecular mechanism of the mechanism of progression and metastasis for PTC is critical for improving the clinical management for patients with advanced PTC. SHCBP1 (SHC SH2 Domain-Binding Protein 1) is first characterized as a protein binging to p52Shc, a subunit of SHC protein, which locates on chromosome 16q11.2 (7). SHCBP1 is evolutionarily conserved in eukaryotes, human SHCBP1 shares 78% identity with mouse's and 23% with the Drosophila melanogaster homolog (8).…”
Section: Introductionmentioning
confidence: 99%
“…SHC SH2 domain-binding protein 1 (SHCBP1), a member of the Src homolog and collagen homolog (SHC) family, plays an essential role in the regulation of multiple signal transduction pathways, such as EGF/EGFR, FGF, NF-κB, MAPK/ERK, PI3K/Akt, TGF-β1/Smad and Wnt/β-catenin [ 3 ]. Increasing evidence has shown that SHCBP1 is involved in the occurrence and development of various types of tumors, accelerating the progression of diseases and facilitating the growth and maintenance of a tumorigenic state.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the downstream targets of miR-33b in RB, we conducted a bioinformatics prediction and characterized SHCBP1 as a possible target. SHCBP1 has been shown to positively regulate tumor progression and its expression remains high in malignant cells 40 . Additionally, high SHCBP1 levels can be observed during the β-selection checkpoint of T cell development, which is necessary for thymic proliferation 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%